Risk of Deep vein thrombosis in neurosurgery: State of the art on prophylaxis protocols and best clinical practices. (November 2017) - Ganau, Mario; Prisco, Lara; Cebula, Helene; Todeschi, Julien; Abid, Houssem; Ligarotti, Gianfranco; Pop, Raoul; Proust, Francois; Chibbaro, Salvatore
Highlights: The majority of DVT developments within the first week after a neurosurgical procedure. The incidence of DVT is greater for cranial (7.7%) than spinal procedures (1.5%). DVT and PE prophylaxis should be tailored individually. Currently, no clear thromboprophylaxis guidelines can be formulated in neurosurgery. Abstract: Objective: To analytically discuss some protocols in Deep vein thrombosis (DVT)/pulmonary Embolism (PE) prophylaxis currently use in Neurosurgical Departments around the world. Data sources: Analysis of the prophylaxis protocols in the English literature: An analytical and narrative review of literature concerning DVT prophylaxis protocols in Neurosurgery have been conducted by a PubMed search (back to 1978). Data extraction: 80 abstracts were reviewed, and 74 articles were extracted. Data analysis: The majority of DVT seems to develop within the first week after a neurosurgical procedure, and a linear correlation between the duration of surgery and DVT occurrence has been highlighted. The incidence of DVT seems greater for cranial (7.7%) than spinal procedures (1.5%). Although intermittent pneumatic compression (IPC) devices provided adequate reduction of DVT/PE in some cranial and combined cranial/spinal series, low-dose subcutaneous unfractionated heparin (UFH) or low molecular-weight heparin (LMWH) further reduced the incidence, not always of DVT, but of PE. Nevertheless, low-dose heparin-based prophylaxis in cranial and spinal series risks minor and major postoperative haemorrhages: 2–4% in cranial series, 3.4% minor and 3.4% major haemorrhages in combined cranial/spinal series, and a 0.7% incidence of major/minor haemorrhages in spinal series. Conclusion: This analysis showed that currently most of the articles are represented by case series and case reports. As long as clear guidelines will not be defined and universally applied to this diverse group of patients, any prophylaxis for DVT and PE should be tailored to the individual patient with cautious assessment of benefits versus risks.